Fortune's faux engagement - Nichols, Carrie (The Fortunes of Texas, 2024)
“You couldn’t possibly be engaged to someone like Heath Blackwood.” Or could she? What in heaven’s name had compelled Jade Fortune to pretend that Heath Blackwood, the most sought-after bachelor in Chatelaine, was her fiancé? Especially when Jade barely knew the start-up titan desperately seeking answers about his own past. But to Jade’s surprise, Heath’s happy to play along with her spur-of-the-moment ruse. This ersatz engagement’s just a figment of Jade's imagination, though. Or could this be the stuff dreams are made of?